الهيئة الشرعية العليا وأثرها على المصارف الإسلامية: دراسة على بعض النماذج في الدول الإسلامية - دكاش، مهند عبد المنعم (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
This thesis is titled “Shari'a Advisory Council and Its Impact on Islamic Banks: A Study of Some Models in Islamic Countries” it discuss the Shari'a advisory council and its impact on Islamic banks through six elements, which are, Shari'a guidelines, Shari'a committees, internal and external Shari'a audit, market and competition among the Islamic banks, judiciary and arbitration institutions in dispute resolution and financial products and finaly the approval mechanism of the new financial products. It has review and compares a number of international models with a focus on the Malaysian and Sudanese models. This thesis use a multiple methodology approach, it use a descriptive approach and comparative analysis approach, where it collecte the information related to the Shari'a Advisory Council and check the laws that governing it, followed by examining the existing information to show the impact of the presence of Share'a Advisory Council on the six elements and then reviewed and compared a number of international models with a focus on the Malaysian and Sudanese experiences and comparing between them. The main findings of this study are as followings; the most important impact of Shari'a Advisory Council on Islamic banks is the standardized of Shari'a guidelines at the state level which leads to the market discipline and the fairness of competition between Islamic banks and finaly the impact of the Shari'a Advisory Council on the Shari'a Commitees is to limit its functions and powers; however, it can not be dispensed with. Another important finding of this study is showing that, although the Sudanese model is older than the Malaysian model but Malaysian model is more advanced and distinct in terms of establishment law, active and impact. Nevertheless, there are many observations about both Malaysian and Sudanese models such as the general and undetailed of membership's requirement, also the lack of details about the legal responsibility of the members in case of their negligence, default or related cases.